LEVELS OF IL-4 AND Γ- INTERFERON IN CHILDREN'S BLOOD SERUM AS PREDICTORS OF ASTHMA FORMATION - Н. Макєєва; В. Андрущенко; В. Малахова; В. Цимбал; Н. Алєксєєва (Bukovynian State Medical University, 2023)
Introduction. The prevalence of asthma continues to increase every year. Asthma is the leading chronic disease. Infl ammation, both acute and chronic, is closely related to the action of cytokines (pro- and anti-infl ammatory). T-helper 2 lymphocytes release IL-4, which triggers the production of immunoglobulin E (IgE) antibodies, which set the stage for allergy and activate infl ammatory cells. The regulators of this process are T helper-1 lymphocytes, which produce cytokines (IFN-gamma) that suppress Th-2 activity. Disturbances in the ratio of Th-1/Th-2 lymphocyte clones are a subject of debate in the early detection of asthma and the prediction of the development of this disease. The aim of the study was to evaluate the levels of IL-4 and γ-interferon in the blood serum of children with transient wheeze and asthma.. Material and methods. 121 children were included in the study. The patients were divided into groups: group 1 - children with transient wheezing (TW) (n = 81), group 2 - children with doctor- diagnosed asthma (DDA) (n = 15), group 3 - healthy children (n = 25). IL-4 and γ-interferon in blood serum were analyzed by ELISA using commercial kits (human IL-4 and human γ-interferon "Vector Best- Ukraine"). Data were analyzed using Statsoft Statistica version 8 (Tulsa, OK) and the MedCalc version 17.2 statistical program. The planned clinical trials were conducted after obtaining the approval of the local ethics committee (date: February 1, 2015; number: 2015/01) and were conducted in accordance with the principles of the Declaration of Helsinki, as amended in October 2013. This article was conducted within the framework of the Department of Pediatrics No. 2 of Kharkiv National Medical University «Medical and biological aspects of adaptation of children with somatic pathology to modern conditions. Prediction of asthma control in children taking into account infl ammatory markers and the state of the airway barrier of the lungs» (state registration number 0120U102471). Results. It was found that in children of the fi rst and second groups, in the midst of clinical manifestations of wheezing, IL-4 levels signifi cantly increased and serum γ-interferon levels decreased. The highest levels of IL-4 and the lowest levels of serum γ-interferon were found in patients with DDA. Serum levels of IL-4 above 15.33 pg/mL and γ-interferon below 98.62 pg/mL in children with wheezing episodes may be considered as a possible indicator of asthma development. Conclusions. Serum IL-4 and γ-interferon are involved in the regulation of allergic infl ammatory processes in the body. A statistically signifi cant increase in IL-4 levels and a decrease in γ-interferon levels in the blood serum of patients with asthma is likely to indicate the development of a chronic form of infl ammation.